Pemanfaatan Data Raster Dalam Menentukan Perubahan Penutupan Lahan Sub Daerah Aliran Sungai (DAS) Biyonga Kabupaten Gorontalo - Novriyal, Feri; Rosalia, Nurma; Botutihe, Nur Meyla Ulfiana; Dunggio, Iswan; Lihawa, Fitryane; Mosi, Yetty (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2024)
This study aims to analyze changes in land cover over a specific period, focusing on the influencing factors and their impacts on the Biyonga Sub-Watershed ecosystem. The method used in this research is a combination of descriptive research method with spatial analysis interpretation approach and field survey. The research findings indicate that spatial analysis of land cover in the Biyonga Sub-Watershed revealed nine land cover classes, such as forest, shrubland, settlements, and agriculture. Land use change patterns were evaluated by overlaying land cover maps from 1990 to 2020. Significant changes in land cover occurred between 1990 and 2000, where secondary dryland forest cover changed to shrubland covering an area of 2,299.98 hectares. For the period 2000-2011, it was found that there was a loss of primary forest cover totaling 2097.27 hectares, which transitioned into secondary dry land forest and shrubland. Other changes included paddy fields transitioning into settlements and dry land agriculture, and dry land agriculture transitioning into settlements. From 2011 to 2020, there was an increase in the area of secondary forest cover and transitions from shrubland and dry land agriculture to secondary forest as well as mixed dry land agriculture.